Representasi Dominasi Perempuan dalam Rumah Tangga: Analisis Tekstual terhadap Situasi Komedi (Sitkom) “Suami-suami Takut Istri” - Sri KUsumo Habsari; Fitria Akhmerti Primasita; M. Taufik Al Makmum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
This article aims at describing how women domination in domestic sphere is represented and exploited—whether to promote feminism or to sustain patriarchy in sitcom Suami-Suami Takut Istri”and what social dan political consequences of such representation have on women's image, men's image, and their relations. It is presented descriptive qualitatively applying textual approach and feminist cultural studies. The analysis shows that women domination is represented and exploited to sustain patriarchal ideology by negatively constructing women power to dominate not as a real domination, in which women can command respect from their domination. The way the women show domination is also constructed negatively, that is by engaging in all kinds of domestic violence. The análysis also shows that such negative construction results in negative image of women and gender relations, but maintains the positive image of men. Thus, in this way, patriarchy is sustained in sitcom Suami-Suami Takut Istri.